Mental health determinants among university lecturers during pandemics: A cross-sectional study in Indonesia - Wiwik Afridah; Fifi Khoirul Fitriyah; Yanesti Nuravianda Lestari; Nur Amin; Edza Aria Wikurendra (Social Sciences and Humanities Open)
During pandemics, anxiety rose significantly among university lecturers. As they adapted to online learning, they were overwhelmed with materials to support students. This study aimed to analyze the factors influencing the mental health of university lecturers during pandemics. The study involved 92 university lecturers. Positive mental health scale (PMH-Scale), physical activity scale (IPAQ), and religiosity and spirituality scale (RSYS) were employed to assess mental health. The data were analyzed using Chi-square and binary logistic regression tests. Physical activity, spirituality, education level, teaching experience, and certification status were significantly linked to the mental health condition. The most influential factors were spirituality, education level, and certification status, which were associated with better well-being and had a significant impact on lecturers’ mental health during the pandemic. The findings of this study highlight the importance of spirituality in maintaining stable mental health during pandemics.